Alkanes from Bioderived Furans by using Metal Triflates and Palladium‐Catalyzed Hydrodeoxygenation of Cyclic Ethers. Issue 24 (27th November 2015) - Song, Hai‐Jie; Deng, Jin; Cui, Min‐Shu; Li, Xing‐Long; Liu, Xin‐Xin; Zhu, Rui; Wu, Wei‐Peng; Fu, Yao
Abstract: Using a metal triflate and Pd/C as catalysts, alkanes were prepared from bioderived furans in a one‐pot hydrodeoxygenation (HDO) process. During the reaction, the metal triflate plays a crucial role in the ring‐opening HDO of furan compounds. The entire reaction process has goes through two major phases: at low temperatures, saturation of the exocyclic double bond and furan ring are catalyzed by Pd/C; at high temperatures, the HDO of saturated furan compounds is catalyzed by the metal triflate. The reaction mechanism was verified by analyzing the changes of the intermediates during the reaction. In addition, different metal triflates, solvents, and catalyst recycling were also investigated. Abstract : Fu, Fu, Fu (tri‐f) : Metal triflates (tri‐f) act as an axe (, Fu), cleaving the C−O bond of cyclic ethers and luckily (, Fu) transforming bioderived furans into alkanes in a one‐pot (, Fu) process. The mechanism of the reaction is verified by analyzing the changes of the intermediates during the reaction. Different metal triflates, solvents, and catalyst recycling are investigated, also.